Risk Factors for Meniscectomy After Meniscal Repair. (December 2013) - Lyman, Stephen; Hidaka, Chisa; Valdez, Ana S.; Hetsroni, Iftach; Pan, Ting Jung; Do, Huong; Dunn, Warren R.; Marx, Robert G.
Background: Previous research suggests that a substantial percentage of meniscal repairs fail, resulting in a subsequent meniscectomy. Risk factors for failure have been investigated using small cohorts, providing ambiguous results. Purpose: To measure the frequency of and elucidate risk factors for subsequent meniscectomies after meniscal repair using a large study population from multiple surgical centers. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 9529 patients who underwent 9609 outpatient meniscal repairs between 2003 and 2010 were identified from a statewide database of all ambulatory surgery in New York. Patients who subsequently underwent a meniscectomy were then identified. A Cox regression analysis was used to calculate the hazard ratio and 95% confidence intervals. The model included patient age, sex, comorbidities, concomitant arthroscopic procedures, laterality of the meniscus, and surgeon's yearly meniscal repair volume. Results: The overall frequency of subsequent meniscectomies was 8.9%. Patients were at a decreased risk for subsequent meniscectomies if they underwent a concomitant anterior cruciate ligament (ACL) reconstruction ( P < .001). Patients undergoing isolated meniscal repairs (without concomitant ACL reconstruction) were at a decreased risk if they were older ( P < .001), had a lateral meniscal injury ( P = .002), or were operated on by a surgeon with a higher annual meniscal repair volume (>24 cases/year; P < .001). Conclusion: A meniscectomy after meniscal repair is performed infrequently, supporting the notion that repairing a meniscus is a safe and effective procedure in the long term. The risk for undergoing subsequent meniscectomies is decreased in patients undergoing a concomitant ACL reconstruction, in cases of isolated meniscal repairs for patients of older age, and in patients undergoing meniscal repair by surgeons with a high case volume.